(untitled) (Czech Journal of International Relations, 2024)
Kai Fischer: Britische Europapolitik. Von Margaret Thatcher zu John Major. AFES-PRESS REPORT, Volume 59. Edited by Hans Giinter Brauch. AFES-PRESS, Mosback1996, 99 stran.